Faktor Penyebab Ketidaklengkapan Pengisian Resume Medis Guna Penunjang Akreditasi di RS Bhayangkara Lumajang - Melati Ayu Pratiwi; Rossalina Adi Wijayanti; Efri Tri Ardianto; Ervina Rachmawati (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2021)
Completeness of medical record 24 hours after completion of service in accordance with the minimum standard of hospital service is 100%, including on the completeness of filling the medical resume form. Based on preliminary studies at Bhayangkara Lumajang Hospital, it was found that one of the unfulfilled standards of MIRM was MIRM 13.4 regarding the completeness of. The researcher checked the completeness of medical resume by taking 265 samples in the quarter I 2019 at Bhayangkara Hospital Lumajang obtained that the overall average medical resume form of completeness was 39%. Average for incompleteness of 54.3%. The purpose of this study is to determine the factors that cause the incompleteness of medical resume replenishment to support accreditation at Bhayangkara Hospital in Lumajang by identifying personnel behavior based on individual, organizational and psychological factors. This type of research is qualitative research. The data collection techniques used are interviews, questionnaires, checklists and documentation. Research results using NGT (Nominal Group Technique) technique obtained priority cause main problem is the limitation of time of the officer in filling the completeness of medical resume from the problem is obtained solution from the result of NGT (Nominal Group Technique) that it needs, monitoring of follow up (specialized areas evaluate completeness).